Determination of Four Major Saponins in Skin and Endosperm of Seeds of Horse Chestnut (Aesculus Hippocastanum L.) Using High Performance Liquid Chromatography with Positive Confirmation by Thin Layer Chromatography - Zead Helmi Mahmoud Abudayeh; Khaldun Mohammad Al Azzam; Ahmad Naddaf; Uliana Vladimirovna Karpiuk; Viktoria Sergeevna Kislichenko (Tabriz University of Medical Sciences, 2015)
urpose: To separate and quantify four major saponins in the extracts of the skin and the endosperm of seeds of horse chestnut (Aesculus hippocastanum L.) using ultrasonic solvent extraction followed by a high performance liquid chromatography-diode array detector (HPLC-DAD) with positive confirmation by thin layer chromatography (TLC). Methods: The saponins: escin Ia, escin Ib, isoescin Ia and isoescin Ib were extracted using ultrasonic extraction method. The optimized extraction conditions were: 70% methanol as extraction solvent, 80 C as extraction temperature, and the extraction time was achieved in 4 hours. The HPLC conditions used: Zorbax SB-ODS-(150 mm × 2.1 mm, 3 m) column, acetonitrile and 0.10% phosphoric acid solution (39:61 v/v) as mobile phase, flow rate was 0.5 mL min-1 at 210 nm and 230 nm detection. The injection volume was 10 L, and the separation was carried out isothermally at 30 C in a heated chamber. Results: The results indicated that the developed HPLC method is simple, sensitive and reliable. Moreover, the content of escins in seeds decreased by more than 30% in endosperm and by more than 40% in skin upon storage for two years. Conclusion: This assay can be readily utilized as a quality control method for horse chestnut and other related medicinal plants.